2013
DOI: 10.1108/ijse-11-2012-0208
|View full text |Cite
|
Sign up to set email alerts
|

Do governance factors matter for happiness in the MENA region?

Abstract: Purpose – Unhappiness has been recognized as one of the main factors that cause political unrest in the Middle East and North Africa (MENA) region in recent years. The purpose of this study is to investigate the effects of governance matters on happiness in the MENA region while controlling for other relevant determinants. Design/methodology/approach – The paper applies panel random effects regression analyses by using data from 14 MENA countries over the period of 2009-2011. Findings – The empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Gholipour Fereidouni et al . () obtained no significant relationship between voice and accountability and happiness in developing MENA countries. Ott () also found that the correlation between happiness and democracy is relatively weak in the MENA region.…”
Section: Major Factors Behind Life Dissatisfaction In Developing Menamentioning
confidence: 86%
“…Gholipour Fereidouni et al . () obtained no significant relationship between voice and accountability and happiness in developing MENA countries. Ott () also found that the correlation between happiness and democracy is relatively weak in the MENA region.…”
Section: Major Factors Behind Life Dissatisfaction In Developing Menamentioning
confidence: 86%
“…The results indicate that the functioning social systems sphere such as healthcare and education is a kind of investment to human capital development that affects national economy and overall social development. Fereidouni et al (2013) analyze the effects of governance issues on happiness and relations between unhappiness and political unrest by using panel data on 14 Middle East and North Africa (MENA) countries, during the period of 2009-2011. The aim of the study is to show the effects of governance components (voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality for private sector development, rule of law and control of corruption) on happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The previous research has shown a positive relationship between the happiness and the various indicators of success in the workplace. Compared to their less happy colleagues, happy people tend to make more money, showing a better job performance, and more often help their colleagues (Boehm & Lyubomirsky, 2008;Lyubomirsky, King, & Diener, 2005).Conversely, the unhappiness in the workplace can reduce the organizational productivity and also increase rates of absenteeism higher in the workplace (Gholipour, Najdi, & Ekhtiari, 2013). It is important that organizations seek the prosperity and the happiness in the workplace, because it is not only benefits for the employees, but also the benefits for the organization, because the happiness in the workplace increases organizational productivity (Fisher, 2010;Rodríguez et al, 2010;Simmons 2014).Jessica Pryce-Jones (in Rao, et al, 2017) adds the happiness in the workplace with regard to utilizing all of the best-owned resources to overcome the challenges faced.…”
Section: Roceeding Of Internationalmentioning
confidence: 99%